Cervicotomy and Sternotomy for Resectin of Cervicothoracic Neuroblastoma in Children - Amine Ksia; Nahla Hmidi; Chokri Kortas; Imen Chabchoub; Sana Mosbahi; Mongi Mekki; Lassaad Sahnoun; Kais Maazoun; Abdellatif Nouri (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2017)
Introduction: We report the case of a 4 years old girl who present a cervico-thoracic ganglioneuroblastome with none response to chemotherapy and radiotherapy Case presentation: The girl was operated using the Cormier Dartevelle-Grünenwald incision which helped to remove the tumor completely with optimal control of noble elements. The follow up was uneventful. Conclusion: The Cormier Dartevelle-Grünenwald incision can be a good option in case of big cervico-thoracic malignant tumors.